2003
DOI: 10.2135/cropsci2003.2058
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sequence Tagged Site and Cleaved Amplified Polymorphic Sequence Markers for Wheat Stripe Rust Resistance Gene Yr5

Abstract: The Yr5 gene confers resistance to all races of the wheat stripe rust pathogen [Puccinia striiformis Westend. f. sp. tritici Eriks. (P. s. tritici)] identified so far in the USA. Cosegregating resistance gene analog polymorphism (RGAP) markers for Yr5 are available but their use requires skills in polyacrylamide gel electrophoresis and may not be polymorphic across various varieties. To develop better markers to be used in marker‐assisted selection for the Yr5 resistance, sequence tagged site (STS) primers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 18 publications
(35 reference statements)
2
40
0
3
Order By: Relevance
“…As Yr76 is race-specific, it should not be used alone. Therefore, combinations of this gene with other widely effective all-stage resistance genes such as Yr5, Yr15, Yr45, Yr53, Yr61, Yr64, Yr65, and YrSP (Chen et al 2003;Feng et al 2015;Li et al 2010;Murphy et al 2009;Xu et al 2013;Zhou et al 2014a), and/or with genes for HTAP resistance such as Yr36, Yr39, Yr52, Yr59, Yr62, and many temporarily named QTL (Carter et al 2009;Chen 2013;Chen 2007, 2009;Lu et al 2014;Ren et al 2012;Uauy et al 2005;Zhou et al 2014b) are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…As Yr76 is race-specific, it should not be used alone. Therefore, combinations of this gene with other widely effective all-stage resistance genes such as Yr5, Yr15, Yr45, Yr53, Yr61, Yr64, Yr65, and YrSP (Chen et al 2003;Feng et al 2015;Li et al 2010;Murphy et al 2009;Xu et al 2013;Zhou et al 2014a), and/or with genes for HTAP resistance such as Yr36, Yr39, Yr52, Yr59, Yr62, and many temporarily named QTL (Carter et al 2009;Chen 2013;Chen 2007, 2009;Lu et al 2014;Ren et al 2012;Uauy et al 2005;Zhou et al 2014b) are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a joint scaling test, while conducting studies on gene action regarding durable, high temperature, adult plant (HTAP) resistance for stripe rust in parental, F1, F2 and backcross popu lations for some crosses in wheat, [24] reported the involvement of epistasis in controlling AUDPC with significant additive additive component. Using generation mean analysis, [25] has reported additive dominance model (absence of epistasis) digenic epistasis with predominant additive gene effect, significant «i» type and «l» type of epistatic interaction for powdery mildew in different cross es of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…By investigating two codominant STS primers; YrSTS7/8 and YrSTS9/10 in 114 BC 7 F 3 lines, Chen et al [33] concluded that these markers are completely linked to Yr5. In another study, Zhang et al [45] applied the YrSTS9/10 marker in a number of isogenic lines (NILs), and found allelic relation between Yr5 and Yr7.…”
Section: Resistance Gene Yr5mentioning
confidence: 99%
“…Based on epidemiological studies, Yr5 is effective against all rust virulent races in North America [11,33,47] and Iran [48]. This gene is known to show high levels of resistance to stripe rust in China [47,49] and Turkey [50].…”
Section: Resistance Gene Yr5mentioning
confidence: 99%
See 1 more Smart Citation